PEMBERDAYAAN POLA HIDUP KONSUMSI DENGAN PRINSIP EKONOMI SYARIAH BAGI NELAYAN SUKU BAJO DIPESISIR PANTAI BAJOE DI KABUPATEN BONE - Samsidar, Samsidar; Samad, Husaini (Jurnal Abdi Insani, 2024)
The aim of this activity is to overcome the dynamics of fishermen's problems in managing their management by providing assistance with scientific studies and education, basic training in managing their consumption patterns so that they can save and increase their income and welfare patterns. Likewise, the pattern of the lending and borrowing system for fishing communities requires assistance regarding the importance of contractual ties as a cooperation agreement between investors and borrowers. As for implementation methods, providing training on managing regular household consumption patterns through training assistance, Focus Group Discussions on how to manage income and usage. "Mengatoro Wassele" application, so that they have data on their results and income and increase the ability of fishermen and retainers/financiers in drafting cooperation agreement concepts. Based on the service activities that have been carried out, the conclusions that can be drawn are as follows: 1. Service in the form of household and consumption management training in the Bajo tribe community with priority for households that have been married for approximately 6 years. 2. Service in the form of assistance in using the MAWAS application, it was found that fishermen's households had difficulty managing their household consumption because they live a more consumptive life and like to spend on things that are less productive and are supported by the culture of the Bajo tribe.